EFFECT OF DIETARY ASTAXANTHIN ON GROWTH, SURVIVAL RATE AND PIGMENTATION OF COMMERCIAL CLOWNFISH, Amphiprion ocellaris - Lam, Ho Son; Vy, Nguyen Tuong; Ngoc, Phan Thi (Vietnam Journal of Marine Science and Technology, 2016)
This study examined the influence of astaxanthin added to food on growth, survival rate and pigmentation of commercial false clownfish, Amphiprion ocellaris. Five experiments were performed with synthetic astaxanthin contents: 0; 50; 100; 150 and 200 mg/kg diets. Mean weight and mean length of fish were 1.16 ± 0.22 gand and 33.05 ± 3.29 mm respectively. Fish were fed by 5% of their live weight during the examination of 8 weeks. After 56 days of experiments, the skin pigmentation levels were analysed using Clownfish Exercise pigmentation chart which has a scale from 1 to 10. Color scales of 5 experiments: 0; 50; 100; 150 and 200 mg Astaxanthin/kg diets were 2.12 ± 0.08, 3.79 ± 0.1, 5.31 ± 0.14, 7.78 ± 0.09, 8.04 ± 0.12 respectively. The result showed that the dietary astaxanthin could increase coloration of skin compared with the control group which had the lightest color (P < 0.05) but there were no significant effects on growth and survival rate of clownfish (P > 0.05).